Determinants of the interruption of exclusive breastfeeding at the 30th day after birth - Daniele Azevedo Kanan de Freitas; Thaymê Pires; Bruna dos Santos Willges; Letícia Daudt; Kimberli Dantas Käfer; Franciele da Silva Martins; Leandro Meirelles Nunes (Sociedade de Pediatria de São Paulo, 2022)
ABSTRACT Objective: To estimate the prevalence of exclusive breastfeeding (EBF), introduction of water, herbal teas, or other milks, as well as to identify the factors associated with the interruption of EBF at the 30th day after birth. Methods: This is a cross-sectional study using structured and pretested questionnaires applied to 310 mothers in two moments: in person, at the maternity ward; and at the time the infant was 30 days of age, by telephone call. Descriptive statistics and multivariate Poisson regression, following a multilevel hierarchical model according to the proximity to the outcome, were used to estimate the association between dependent and independent variables. Results: The maintenance of EBF at 30 days of age of the infant occurred in 85.2% of the sample, 1.6% receiving water, 11.5% herbal teas, and 8.2% other milk. Predictors for EBF interruption in the univariate analysis were the mothers' return to work or study activities shortly after the baby's birth (IR 2.88; 95%CI 1.14-7.25) and the use of a pacifier (IR 3.29; 95%CI 1.52-6.22). The interruption of EBF was lower in the group of participants who received support from the infant's maternal grandmother (IR 2.71; 95%CI 1.11-6.56) and their partner (IR 4.78; 95%CI 1.90-12.06). After a multivariate analysis, only the use of a pacifier (IR 5.47; 95%CI 2.38-19.3) and the partner's support (IR 6.87; 95%CI 2.04-23.1) maintained the association with the outcome. Conclusions: The prevalence of EBF found in this study can be considered good, and future interventions aimed at increasing the duration of EBF in this population should take into account the participation of the partner and the reinforcement for not introducing the pacifier.